DEVELOPING DIGITAL MODULE USING FLIP PDF PROFESSIONAL TO FACILITATE STUDENTS’ MATHEMATICAL COMMUNICATION SKILLS ON NUMBER PATTERN MATERIAL - Sinta Dwi Lestari; Palupi Sri Wijayanti (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2021)
This study aims to develop a digital module using Flip PDF Professional to facilitate students' mathematical communication skills through contextual problems. This research is Research & Development (R&D). The development model used is the ADDIE development model. The stages in the development model are analysis, design, development, implementation, and evaluation. The digital module was piloted to class VIII A MTs Al Ichsan students for the 2020/2021 academic year. The module was compiled to meet the valid, practical, and effective criteria. Based on the results of the study, it was obtained that (1) The digital module is declared “valid” with an average expert score of 88% with the “excellent” criteria. (2) The digital module is declared “practical” with an average score percentage of 90% with the “excellent” criteria. (3) The digital module is declared “effective” with an average score percentage of 88% with the “excellent” criteria. The analysis results of the effectiveness of the digital module to facilitate mathematical communication skills show that the average test results of students are more than the minimum completeness criteria. This module can be further developed by other researchers discussing different materials or made even more exciting and developed using other application assistance.